Haiti : Enhanced Initiative for Heavily Indebted Poor Countries; Preliminary Document. (IMF Staff Country Reports; Country Report ;, 2006)
This paper presents a preliminary assessment of the eligibility of Haiti for assistance under the Enhanced Heavily Indebted Poor Countries Initiative (HIPC) to attain the Millennium Development Goals (MDGs). It discusses the medium-to-long-term macroeconomic framework, poverty, social, and political developments of Haiti, and summarizes the results of the preliminary Debt Sustainability Analysis (DSA) and possible HIPC and Multilateral Debt Relief Initiative (MDRI) assistance. It suggests a timeline for the preparation of the decision point document, presents key reforms for the completion point triggers, and gives an indication of how prospective HIPC assistance will be used and its use tracked.